The Influence of Transformational Leadership on Employee Performance With Readiness to Change as a Mediation Variable - Manuk, Nur Alifah Ensa Putri; Asfiyah, Nurul; Febriani, Rizki (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study aims to study how Employee Performance is affected by Transformational Leadership using Readiness to Change as a mediator. The method used in this study is Partial Least Square (PLS), and it includes 54 employees of PT Bank BRI KC Malang Kawi. This research reveals that Transformational Leadership has a positive and significant impact on employee performance, and also shows a significant positive correlation with readiness to change. Apart from that, Readiness to Change has a positive and significant effect on Employee Performance. Readiness to Change is also a full mediator in the relationship between Transformational Leadership and Employee Performance.